2011
DOI: 10.1089/mdr.2010.0162
|View full text |Cite
|
Sign up to set email alerts
|

Group AStreptococcusAntibiotic Resistance in Southern Brazil: A 17-Year Surveillance Study

Abstract: This polyclonal spreading of cMLS(B) macrolide resistance has not been previously observed in South America and should stimulate further epidemiological surveillance in this part of the world.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
3
3
2
Order By: Relevance
“…The tetracycline resistance rate was lower than that observed in a study conducted in Brazil one decade ago, in which the authors reported 43.1% resistance ( D‘Oliveira et al 2003 ). Instead, it was very similar to recent data from southern Brazil and Portugal ( Torres et al 2011 , Friães et al 2012 ). However, 73% resistance to this antimicrobial was reported in a recent study from India ( Mathur et al 2014 ).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The tetracycline resistance rate was lower than that observed in a study conducted in Brazil one decade ago, in which the authors reported 43.1% resistance ( D‘Oliveira et al 2003 ). Instead, it was very similar to recent data from southern Brazil and Portugal ( Torres et al 2011 , Friães et al 2012 ). However, 73% resistance to this antimicrobial was reported in a recent study from India ( Mathur et al 2014 ).…”
Section: Discussionsupporting
confidence: 90%
“…Regarding erythromycin and clindamycin resistance, the rates found here far exceeded those previously reported in the same geographical area ( D‘Oliveira et al 2003 , Torres et al 2011 ), but they are very similar to those described in some recent studies conducted in Europe ( Friães et al 2012 , Syrogiannopoulos et al 2013 ). While a trend of decreasing erythromycin resistance has been recently observed in Spain and Taiwan ( Huang et al 2014 , Montes et al 2014 ), the resistance rates in our study fluctuated over the years.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…S. pyogenes isolates are uniformly susceptible to penicillin but have demonstrated resistance to other classes of antimicrobials, including macrolides, tetracyclines, and lincosamides (13). Epidemiological surveillance of S. pyogenes in Canada has identified emm type 1 as its leading cause of invasive infections (4).…”
Section: Genome Announcementmentioning
confidence: 99%